Lifetime-Based Sensing of Glucose Using Energy Transfer with a Long Lifetime Donor - Tolosa, Leah (Anal Biochem, 1997)
We describe an optical assay for glucose based on the luminescence decay time of a long lifetime metal–ligand complex. Concanavalin A was covalently labeled with Ruthenium metal–ligand complex (RuCon A) which served as the donor. The acceptor was malachite green which was covalently linked to insulin. The malachite green insulin was also covalently labeled with maltose (MIMG) to provide binding affnity to RuCon A. Binding of RuCon A to MIMG resulted in a decreased intensity and decay time of RuCon A. Glucose was detected by competitive displacement of MIMG from RuCon A, resulting in increased intensity and decay time. This glucose assay has several favorable features. The long life time of RuCon A allows phase-modulation decay time measurements using an amplitude-modulated blue-light-emitting diode as the light source. Reversibility of the assay can be controlled by the extent of sugar labeling of the insulin. Finally, the glucose-sensitive range can be adjusted by selection of the sugar structure and extent of labeling of the insulin.